2000
DOI: 10.1177/001979390005300204
|View full text |Cite
|
Sign up to set email alerts
|

What Does Affirmative Action Do?

Abstract: The authors use data from a survey of employers to investigate how Affirmative Action in recruiting and hiring influences hiring practices, personnel policies, and ultimately employment outcomes. They find that Affirmative Action increases the number of recruitment and screening practices used by employers, raises employers' willingness to hire stigmatized applicants, increases the number of minority or female applicants as well as employees, and increases employers' tendencies to provide training and formally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 21 publications
3
78
0
1
Order By: Relevance
“…The regulation may produce a (psychological) reaction inside the boardroom, undermining statistical or taste‐based discrimination. This possibility would echo the findings by Holzer and Neumark (), who observed, using a U.S. survey of employers, an increase in training effort toward women and minorities in workplaces practicing Affirmative Action plans in hiring: while the regulation acted as a constraint on the hiring practices of employers, the latter have reacted by enhancing investments in minorities’ human capital. In our setting, it would lead companies to move on, giving up discriminatory practices based on gender stereotypes.…”
Section: Institutional Setting and Research Questionsupporting
confidence: 57%
“…The regulation may produce a (psychological) reaction inside the boardroom, undermining statistical or taste‐based discrimination. This possibility would echo the findings by Holzer and Neumark (), who observed, using a U.S. survey of employers, an increase in training effort toward women and minorities in workplaces practicing Affirmative Action plans in hiring: while the regulation acted as a constraint on the hiring practices of employers, the latter have reacted by enhancing investments in minorities’ human capital. In our setting, it would lead companies to move on, giving up discriminatory practices based on gender stereotypes.…”
Section: Institutional Setting and Research Questionsupporting
confidence: 57%
“…To level the playing field, organizations around the globe have implemented affirmative action plans (AAPs), which are policies designed to improve work outcomes for underrepresented groups by providing them with extra help in the employment process (Jain, Sloane, & Horwitz, 2003;Yang, D'Souza, Bapat, & Colarelli, 2006). AAPs increase the number of women and ethnic minorities in managerial positions (Holzer & Neumark, 2000;Kalev, Dobbin, & Kelly, 2006;Leonard, 1984), and thus help promote organizational diversity and redress societal injustice. 1 Nevertheless, AAPs are not without drawbacks.…”
mentioning
confidence: 99%
“…Given that affirmative action policies are thought to attenuate social hierarchies (Chow, Lowery, & Knowles, ) and were designed to increase the representation of minority groups in organizations (Holzer & Neumark, ), it is not surprising that past research has found a negative relationship between SDO and affirmative action policy support across a wide range of samples (e.g., Pratto, Sidanius, Stallworth, & Malle, ; Sidanius & Pratto, ; Federico & Sidanius, ). In other words, both theoretically and empirically, antiegalitarians tend to oppose affirmative action policies to a greater extent than egalitarians.…”
Section: Antiegalitarians Against Affirmative Actionmentioning
confidence: 99%